Incorporation of Essential Oils and Nanoparticles in Pullulan Films to Control Foodborne Pathogens on Meat and Poultry Products. Issue 4 (12th March 2014) - Morsy, Mohamed K.; Khalaf, Hassan H.; Sharoba, Ashraf M.; El‐Tanahi, Hassan H.; Cutter, Catherine N.
Abstract The incorporation of essential oils and nanotechnology into edible films has the potential to improve the microbiological safety of foods. The aim of this study was to evaluate the effectiveness of pullulan films containing essential oils and nanoparticles against 4 foodborne pathogens. Initial experiments using plate overlay assays demonstrated that 2% oregano essential oil was active against Staphylococcus aureus and Salmonella Typhimurium, whereas Listeria monocytogenes and Escherichia coli O157:H7 were not inhibited. Two percent rosemary essential oil was active against S. aureus, L. monocytogenes, E. coli O157:H7, and S. Typhimurium, when compared with 1%. Zinc oxide nanoparticles at 110 nm were active against S. aureus, L. monocytogenes, E. coli O157:H7, and S. Typhimurium, when compared with 100 or 130 nm. Conversely, 100 nm silver (Ag) nanoparticles were more active against S. aureus than L. monocytogenes. Using the results from these experiments, the compounds exhibiting the greatest activity were incorporated into pullulan films and found to inhibit all or some of the 4 pathogens in plate overlay assays. In challenge studies, pullulan films containing the compounds effectively inhibited the pathogens associated with vacuum packaged meat and poultry products stored at 4 °C for up to 3 wk, as compared to control films. Additionally, the structure and cross‐section of the films were evaluated using electron microscopy. The results from this study demonstrate that edible films made from pullulan and incorporated with essential oils or nanoparticles may improve the safety of refrigerated, fresh or further processed meat and poultry products.